Mycena pseudopicta (J.E. Lange) Kühner, a rare graminicolous species growing on Poaceae - Moreno Horcajada, Gabriel; Heykoop Fung-A-You, Michel (Revista Catalana de Micologia, 2007)
Mycena pseudopicta (J .E. Lange) Kühner, a rare graminicolous species growing onPoaceae. Mycena pseudopicta, a rare species from section Cinerellae Singer ex Maas Geest., ocurring inSpain, is described and illustrated macro- and microscopically. It is characterized by its stronglydecurrent gills, its cheilocystidia with fairly long and coarse excrescences and its graminicolous habitat.